Geographic diversification in banking - Fang, Yiwei; van Lelyveld, Iman (Journal of Financial Stability, 2014)
In the aftermath of the 2007–2009 crisis, banks claiming positive diversification benefits are being met with skepticism. Nevertheless, diversification might be important and sizable for some large internationally active banking groups. We use a universally applicable correlation matrix approach to calculate international diversification effects, in which bank subsidiaries are treated as individual assets of the banking group portfolio. We apply the framework to 49 of the world's largest banking groups with significant foreign business units over the 1992–2009 period. Focusing on the most important risk in banking, credit risk, we find that allowing for geographical diversification could reduce banks’ credit risk by 1.1% on average, with risk reduction ranging from negligible up to 8%.